Healing Pain through Dance: A Critical Reading of Adhikari’s “Khuchching!” - Pokharel, Badri Prasad (Tribhuvan University Journal, 2020)
This paper makes an attempt to analyze the healing pain through dance in Dinesh Adhikari’s poem “Khuchching” by applying cultural trauma perspective. The poem’s idea is similar to New Zealand’s tribal dance Haka. The poem shows a poor and insurgency affected persona living with traumatic experience and fleeing away from his grief and finally takes refuge to dance which helps him relieve with pains and suffering. Similarly, Haka, a traditional dance of a tribal group – Maori, is performed to pacify the pain and helps them strengthen themselves to face more challenges and strife courageously. In doing so, I have used the critical insight of Caruth as well as cultural ingredients of Haka dance as theoretical parameters to analyze the primary text. Here, I examine the poem linking it with the aim of performing the tribal dance Haka which would, subsequently, help one get relief from personal trauma to the conflict generated consequences in the lives of affected people and their socio-political factors associated with contemporary Nepali society. Discussing the expected findings, this article centers on the common people’s aspirations and embedded peace in the society.